Interdependence investigation of dynamic between the von Willebrand factor and erythrocyte and leukocyte intoxication indices in experimental peritonitis - Savytskyi, I. V.; Tsypoviaz, S. V.; Lenik, R. G.; Bilash, O. V.; Zashchuk, R. H.; Miastkivska, I. V.; Zaiats, L. M. (Journal of Education, Health and Sport, 2019)
The research was conducted on 175 white rats of reproductive age (3 months), weight of animals - 180-220 g. Animals were divided into 4 groups: Group 1 - 20 intact animals. Group 2 - 50 rats with simulated fecal peritonitis. Group 3 - 50 rats with simulated fecal peritonitis with subsequent antibiotic correction and debridement by chlorhexidine solution. Group 4 - 50 rats with simulated fecal peritonitis with subsequent antibiotic correction, chlorhexidine debridement and endothelial dysfunction correction with the use of a nitric oxide donor. Fecal peritonitis was modeled using injection of 10% fecal suspension in a dose of 0.5 ml per 100 g of animal weight in the abdominal cavity of laboratory animals by puncture method (Lazarenko V.A., et al., 2016, patent No. 233826). The following results were obtained. Endothelial dysfunction is the trigger mechanism of vascular catastrophes after experiencing experimental peritonitis. Evidence of endothelial functional status impairment during experimental peritonitis is a significant increase in the level of Willebrand factor in the animals blood flow (p <0.001). It was revealed significant increase in erythrocyte intoxication index (EII). It has been proved increase in leukocyte intoxication index (LII) in experimental animals during simulated peritonitis. It has been confirmed effectiveness of nitric oxide donor use in the complex correction of peritonitis and endothelial dysfunction as its complication is confirmed.